Diffusional protection of electrode surfaces using regular arrays of immobilised droplets: overcoming interferences in electroanalysis. - Simm, A; Ordeig, O; Del Campo, J; Muñoz, F; Compton, R (2006)
Regular arrays of ca. micron sized droplets on a gold electrode surface can block diffusion to the electrode surface of one metal ion (which binds with the material in the droplet) whilst having no significant effect on another (which does not), so allowing interference effects in electroanalysis to be eliminated.